Contrastive Analysis of Vowel Production in Hindi and Malayalam Learning Infants - Roy, Reeny; N., Sreedevi (International Journal For Research In Educational Studies, 2019)
Infants begin to vocalize as early as they are born. Speech like vocalizations such as gurgles, shrieks are also accompanied. Parent and caregiver interaction during this period are vital for early pre linguistic vocalizations. Early vocalizations are usually vowel like forms. The researcher’s previous studies focused on vowel production in Hindi and Malayalam learning children. However, in this locus, it is exciting to compare and contrast the early vowel productions in both these language learning infants. The present paper focusses on analyzing the contrastive features of vowel production in 4 to 12 month -old infants in Hindi and Malayalam language. The participants consisted of 80 typically developing native speaking Hindi and Malayalam infants. The audio recordings were carried out and transcribed. The transcribed data was analyzed in IPA to acquire the frequency of the vowel productions.